Formulasi Sediaan Lotion Antioksidan Ekstrak Daun Sirsak (Annona muricata L.) dan Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) sebagai Pelembab - Sumardi; Suprianto; Innayah Azzahra; Lisa Syafrida (Jurnal Indah Sains dan Klinis, 2025)
Background: A lotion made from ethanol extracts of Sirsak (Annona muricata) leaves and Naga Merah fruit (Hylocereus polyrhizus) peels is a potential antioxidant moisturizer, but its quality, safety, and hydration effect need confirmation. Objective: To formulate five oil-in-water lotions with different extract ratios (total extract 3% w/w) and evaluate physical quality, preliminary safety, and moisturizing performance. Method: The formulations were tested for organoleptic properties, homogeneity, pH, and spreadability. A simple irritation test and a three-day forearm hydration assessment using a skin analyzer were conducted in 25 panelists, followed by one-way analysis of variance. Results: All formulations had pH 6.67–6.96, with minor inhomogeneity observed in one formulation. Acceptable spreadability was achieved by three formulations under specific loads. No irritation occurred. All formulations increased hydration, with significant differences between them (p < 0.001); the two best-performing formulations produced the highest and most stable moisture over three days. Conclusion: The combined-extract oil-in-water lotion at 3% w/w is feasible and preliminarily safe, and the two top formulations are recommended for further development